Chondrichthyans from the Grippia bonebed (Early Triassic) of Marmierfjellet, Spitsbergen - Bratvold, Janne; Delsett, Lene Liebe; Hurum, Jørn Harald (Norwegian Journal of Geology, 2018)
The Grippia bonebed is located at Marmierfjellet in Flowerdalen, Isfjorden area of Spitsbergen. The bonebed occurs in the Vendomdalen Member, Vikinghogda Formation, Early Triassic (Spathian). It is unique in Spitsbergen because of the richness of chondrichthyans, osteichthyes, amphibians and ichthyopterygians. This paper focuses on the chondrichthyans with more than 550 chondrichthyan teeth studied, together with three fin spines and one cephalic spine, assigned to 7 genera and 15 species, 8 of which are new from the Grippia niveau. The Hybodontiformes represent five of the identified genera, where most of the identified species belong to Hybodus and Acrodus. Hybodus sasseniensis, previously recorded from the older Dienarian substage, and is now shown to occur in the younger Spathian substage, and suggested to be the senior synonym of H. rapax. The possibility of Acrodus scaber and A. spitzbergensis being morphospecies, and the Acrodus genus in general, is further discussed. The occurrence of Hybodus microdus in the material is uncertain since it is shown that the mesio-distal length of the teeth is much larger than described by Stensio in 1921. The Neoselachii (modern shark), previously only known from a fin spine of Nemacanthus from the Triassic of Spitsbergen, is now described from teeth belonging to possibly two new neoselachian species. They are referred to Synechodontiformes 1 and 2, awaiting more material to be processed.